Geothermal energy, heat exchange systems and energy piles - Craig, William; Gavin, Kenneth (ICE Publishing, 2018)
'Geothermal Energy, Heat Exchange Systems and Energy Piles' focuses on topics from high temperature geothermal energy extraction, to lower temperature situations at ground surface and shallow depths. Providing broad international coverage, the chapters encompass field observations on sites in several countries as well as computational and laboratory studies. Ground conditions vary from hard rock to chalk, loess to London Clay.
Previously issued in print in 2018. Digital resource published 2018.
Keywords: Geothermal engineering.; elektronické knihy; electronic books